CS-6-induced p62 accumulation exacerbates DNA damage in colorectal cancer - Yitong Gong; Yitong Gong; Menghan Dong; Xiaofei Feng; Xiaofei Feng; Naiyu Zhang; Xuehui Cui; Liushuyue Wang; Qi Qi; Chiu-fai Kuok; Qingling Jiang; Sixue Bi (Frontiers in Pharmacology)
BackgroundGamabufotalin (CS-6), a bufadienolide derived from Chansu, has been reported to exhibit anti-tumor effects in various cancers, including glioblastoma, nonsmall cell lung cancer, and breast cancer. However,its role in colorectal cancer (CRC) remains unexplored.ObjectiveOur study aimed to evaluate the inhibition of CS-6 to CRC cells by cell viability assay, colony formation assay, comet assay, and cell cycle analysis firstly. And its molecular mechanism was studied by immunofluorescence (IF) assay, western blot (WB) assay, siRNA transfection, protein-protein interaction (PPI) network and co-immunoprecipitation (Co-IP) assay. Finally, the in vivo antitumor assessments of CS-6 on colorectal cancer was validated through an transplant colorectal cancer model.ResultsCS-6 treatment significantly inhibited CRC SW620 and DLD1 cell viability and colony formation in vitro. Furthermore, CS-6 treatment-induced DNA damage and cell cycle arrest in SW620 and DLD1 cells. The western blot assay revealed that CS-6 treatment upregulated p62 expression. Knockdown of p62 in this study significantly alleviated CS-6-induced DNA damage and the downregulation of cyclin expression in SW620 and DLD1 cells. Additionally, the results indicated increased expression of microtubuleassociated protein I/II light chain 3II (LC3II) and reduced binding between B-cell lymphoma-2 (Bcl2) and beclin-1, suggesting that CS-6 treatment activated early-stage autophagy in CRC cells. However, inhibition of latestage autophagy and autophagy-related protein 5 (ATG5) with chloroquine and si-ATG5, respectively, further indicated that CS-6-induced autophagy defects led to p62 accumulation, exacerbated cell proliferation inhibition, and aggravated DNA damage. Intraperitoneal injection with CS-6 inhibited tumor growth in nude mice with colorectal cancer, and promoted the protein expression of phosphorylated H2A histone family member X (γH2AX), p62, phosphorylated Ataxia-telangiectasia mutated kinase (p-ATM) and LC3 I/II.ConclusionThis study suggests that CS-6 may exert its anti-tumor effects in CRC by inducing autophagy defects, resulting in p62 accumulation and DNA damage in vitro and in vivo.